Excise Taxation for Domestic Resource Mobilization - Sijbren Cnossen (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Most governments will have to raise additional resources to deal with the aftermath of the corona crisis. This paper argues that excise duties on drinking, smoking, gambling, sugar-sweetened beverages, plastics, fossil fuels, motoring, telecoms and platforms are the preferred instruments. In nearly all cases, excise duties improve the efficient allocation of resources, while reliance on them is consistent with an equitable tax system. Also, excise duties can be administered more easily than income and value added taxes. Current excise duties are way below efficient levels. It should be possible to triple their yield, especially in developing countries.
Keywords: H21; H23; H25; 330; excise duties; resource mobilization; smoking; drinking; gambling; sugar-sweetened beverages; plastics; fossil fuels; motoring; telecoms; platforms; luxury consumption